Transformasi Gender: Strategi Pembebasan Perempuan dari Jerat Pembangunan dan Kapitalisme - Nurus Shalihin; Firdaus Firdaus (Sawwa: Jurnal Studi Gender, 2019)
Indonesia has long been aware of the importance of gender equality through accommodating women's public rights and recognizing the importance of women's position in development. However, the efforts have not been fully able to create equal and fairness relations between men and women. This conceptual paper is the purpose to explore the main issues in order to develop gender equality relations in Indonesia. Through the study of existing literature, the authors find two main issues on gender equality development in Indonesia. First, the problem of human resources development policy that not yet based on empowerment oriented. Second, the penetration capitalism on placed the women in not favorable position. In order to solve the two main problems, authors offer a gender transformation as strategies to raise gender equality.